Schizophrenia susceptibility gene dysbindin regulates glutamatergic and dopaminergic functions via distinctive mechanisms in Drosophila. - Shao, L.; Shuai, Y.; Wang, J.; Feng, S.; Lu, B.; Li, Z.; Zhao, Y.; Wang, L.; Zhong, Y. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
The dysfunction of multiple neurotransmitter systems is a striking pathophysiological feature of many mental disorders, schizophrenia in particular, but delineating the underlying mechanisms has been challenging. Here we show that manipulation of a single schizophrenia susceptibility gene, dysbindin, is capable of regulating both glutamatergic and dopaminergic functions through two independent mechanisms, consequently leading to two categories of clinically relevant behavioral phenotypes. Dysbindin has been reported to affect glutamatergic and dopaminergic functions as well as a range of clinically relevant behaviors in vertebrates and invertebrates but has been thought to have a mainly neuronal origin. We find that reduced expression of Drosophila dysbindin (Ddysb) in presynaptic neurons significantly suppresses glutamatergic synaptic transmission and that this glutamatergic defect is responsible for impaired memory. However, only the reduced expression of Ddysb in glial cells is the cause of hyperdopaminergic activities that lead to abnormal locomotion and altered mating orientation. This effect is attributable to the altered expression of a dopamine metabolic enzyme, Ebony, in glial cells. Thus, Ddysb regulates glutamatergic transmission through its neuronal function and regulates dopamine metabolism by regulating Ebony expression in glial cells.